Answer:
Pregunta muy difícil, no creo que pueda resolver este amigo.
Step-by-step explanation:there is no step-by-step thing because honestly don't understand what your trying to say here. Hmm...
It’s should be 12.04 after you do all the math and add it up
The answers are #1 45 #2 24 #3 10
Answer:
(-2,-3) and (3,2)
Step-by-step explanation:
sub in x-1 into y
x^2 + (x-1)^2 = 13
x^2 + (x-1)(x-1)=13
x^2 + x^2 -2x +1 = 13
2x^2 -2x-12=0
solve for x by factoring (quadratic formula, product sum etc..)
x= -2 and 3
plug in those values into y=x-1 and solve for y